2011
DOI: 10.1590/s0100-40422011000200021
|View full text |Cite
|
Sign up to set email alerts
|

Glicoalcaloides antifúngicos, flavonoides e outros constituintes químicos de Solanum asperum

Abstract: Recebido em 7/6/10; aceito em 11/8/10; publicado na web em 26/11/10 ANTIFUNGAL GLYCOALKALOIDS, FLAVONOIDS AND OTHER CHEMICAL CONSTITUENTS OF Solanum asperum Rich (Solanaceae). Two glycoalkaloids: solamargine and solasonine; three flavonoids: tiliroside, 7-O-α-L-ramnopyranosyl-kaempferol and, in addition to the tripeptide Leu-Ile-Val, the aminoacid proline and the eicosanoic acid were isolated from Solanum asperum (Solanaceae). The structures of all compounds were determined by interpretation of their spectra (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
8
0
6
Order By: Relevance
“…Rob., which has shown strong antifungal properties against T. mentagrophytes (Portillo et al 2005). Antifungal activity has also been proven for alkaloid derivatives-glycoalkaloids (Pinto et al 2011;Medeiros et al (2011). One of the more widely studied compounds in this group with high toxicity to dermatophyte cells, including T. rubrum, are solamargine, solasonine and a-solanine (Fewell and Roddick 1997;Pinto et al 2011).…”
Section: Alternative and New Forms Of Therapymentioning
confidence: 99%
“…Rob., which has shown strong antifungal properties against T. mentagrophytes (Portillo et al 2005). Antifungal activity has also been proven for alkaloid derivatives-glycoalkaloids (Pinto et al 2011;Medeiros et al (2011). One of the more widely studied compounds in this group with high toxicity to dermatophyte cells, including T. rubrum, are solamargine, solasonine and a-solanine (Fewell and Roddick 1997;Pinto et al 2011).…”
Section: Alternative and New Forms Of Therapymentioning
confidence: 99%
“…Although the development of solasonine (Coramsine, SBP002) to be a new drug was failed, its initial clinical trials were promising. In addition, solasonine has antifungal [7], antiparasitic [8], antidiabetic [9], cytolysis [10] and antihepatitis B virus [11] effects. As such, more and more scholars are paying attention to the pharmacological activities of solasonine.…”
Section: Introductionmentioning
confidence: 99%
“…3 Structurally, SN and SM share a common steroidal aglycone, solasodine, which has been used for the production of steroidal drugs. 4 Previous studies have shown that these glycoalkaloids display antifungical, 5,6 schistosomicidal, 7 antiprotozoal, 8 molluscicidal, 9 antiviral, 10 antimutagenic, 11 and antineoplasic activities against a variety of neoplastic cell lines, [12][13][14] as well as hypoglycemic and gastric emptying inhibitory activities. 15 As stated by Gottlieb and collaborators, 16 Brazilian biodiversity is an important source of wealth, and its benefits do not only depend on the use of biodiversity, but also in its sustainability for proper economic exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, topical and transdermal drug delivery provides several potential advantages in comparison to other administration routes, since the first-pass hepatic metabolism is avoided leading to fewer side effects. 17 Studies have highlighted the biological potential of the glycoalkaloids, SN and SM, against topical diseases such as herpes, 10 dermatophytes 6 and skin cancer. 14 Nevertheless, no studies are available assessing the penetration of these compounds into/through the skin.…”
Section: Introductionmentioning
confidence: 99%